Kánaán és Mars-mező: Fazekas Mihály két versének közköltészeti kapcsolatai - Csörsz, Rumen István (Studia Litteraria, 2020)
Mihály Fazekas had the chance to get to know several layers of Hungarian popular poetry in the Reformed College in Debrecen, as well as during his soldier years and in the end after he returned to his homeland. Although his popular poems are not as complex as the songs of the contemporary poets, Ádám Pálóczi Horváth and Mihály Csokonai Vitéz, in a few cases it is clear that he was inspired by one or more popular songs, and he wrote his poems following these models or launching a dialogue with them. The study tries to explore the background of the most famous two poems of Fazekas. The source and prefiguration of Hortobágyi dal ’Hortobágy Song’ (’O blessed Canaan’) was a drinking song with similar open formulas which was very popular until 1800 in Debrecen, as well as in Transdanubia, paraphrased to the region of lake Balaton. A little detail of the Hortobágy Song was torn off from the text by Fazekas and spread as an anonymous popular song after 1820 (just in the life of the author!) as Betyár Dal ’Outlaw Song’. Its English translation was published in the anthology of John Bowring (Poetry of the Magyars, London, 1830). The other poem, the Katonai búcsúének ’Military Farewell Song’ (‘Armies, who often sweat in the workshop of Mars, on the battlefield’) was written after Fazekas was promoted to lieutenant in 1796 and he disarmed unexpectedly. He bids farewell to the excruciating soldier life, which although promises the palm branch of victory, and imitates the rhythm and melody of the contemporary Hungarian marches, in a way writing a counter-song to the tune of trumpets.